2016
DOI: 10.1073/pnas.1610844113
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Golgi disassembly is required for bipolar spindle formation and mitotic progression

Abstract: During mitosis, the mammalian Golgi vesiculates and, upon partitioning, reassembles in each daughter cell; however, it is not clear whether the disassembly process per se is important for partitioning or is merely an outcome of mitotic entry. Here, we show that Golgi vesiculation is required for progression to metaphase. To prevent Golgi disassembly, we expressed HRP linked to a Golgi-resident protein and acutely triggered the polymerization of 3,3′-diaminobenzidine (DAB) in the Golgi lumen. The DAB polymer do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 64 publications
(80 reference statements)
2
46
1
Order By: Relevance
“…The exact molecular links that account for this hierarchical relationship are elusive, requiring further in‐depth investigation. Cells expressing ER‐ or GA‐targeted HRP and treated with DAB/H 2 O 2 exhibited local DAB precipitation before they died, indicating that ER and/or GA perturbations are sufficient for cell killing, perhaps due to the perturbation of GA trafficking (Jollivet et al , ) and dynamics (Guizzunti & Seemann, ).…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular links that account for this hierarchical relationship are elusive, requiring further in‐depth investigation. Cells expressing ER‐ or GA‐targeted HRP and treated with DAB/H 2 O 2 exhibited local DAB precipitation before they died, indicating that ER and/or GA perturbations are sufficient for cell killing, perhaps due to the perturbation of GA trafficking (Jollivet et al , ) and dynamics (Guizzunti & Seemann, ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of ribbon disassembly, by interfering with the Golgi Reassembly Stacking Protein GRASP65 delays progression through the G2/M transition indicating that the change in Golgi morphology feeds into the cell cycle machinery pathway. Moreover, inhibition of the Golgi ribbon disassembly, by accumulation of a polymer of diaminobenzidene (DAB) in the Golgi lumen which inhibits membrane re‐modeling, arrests cells in early mitosis . The arrested cells lacked a bipolar spindle, had unseparated centrosomes, and had an active spindle assembly checkpoint.…”
Section: The Golgi As a Cell Sensormentioning
confidence: 99%
“…He further showed that (Ferraro et al, 2016). Changes in Golgi organization, in particular its disassembly in early mitosis, also appear to have a role in controlling mitotic spindle assembly, as shown by Joachim Seemann (UT Southwestern, Dallas, USA) (Guizzunti and Seemann, 2016).…”
Section: Secretion: Making Proteins and Membranes And How To Get Themmentioning
confidence: 92%